Translating Sacred Scriptures in Sundanese: A Comparative Analysis of the Bible and the Qur’an in West Java, Indonesia - Roni Nugraha; Intan Permanik; Jajang A Rohmana (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
This study critically examines the various characteristics of the Sundanese translations of the Bible and the Qur’an. It focuses on two translations of each scripture—S. Coolsma’s 1891 and the LAI 1991 editions of the Bible, alongside Miwah Tarjamahna (2002) and MORA (2020) translations of the Qur’an. Using library research and employing Venuti’s theory of foreignization-domestication, as well as Vermeer’s Skopos theory, this study examines linguistic orientations in both target and source languages. The findings reveal significant distinctions in translation strategies. Bible translations into Sundanese predominantly adopt domestication strategies, emphasizing fluency and accessibility in the target language. In contrast, the Qur’anic translations preserve source language structures through foreignization, reflecting fidelity to original Arabic forms. These tendencies are shaped not only by textual and doctrinal considerations but also by historical and sociolinguistic contexts. Specifically, Bible translations are characterized by colloquial expression and dynamic shifts in Indonesian Bible translation movements, while Qur’anic translations maintain formal diction and syntactic patterns rooted in Arabic. The analysis further identifies lexical, semantic, and syntactic patterns that reveal each scripture’s translation ideology. These differences illustrate how theological authority, religious tradition, and institutional policy influence linguistic choices. The study highlights the importance of understanding translation as a cultural and ideological act, particularly in multilingual and multi-religious regions such as West Java.